(untitled) (Journal of actual problems of jurisprudence, 2022)
The entire process of development and prosperity of the Republic of Kazakhstan in the last decade is aimed at creating a socializing state. It is always obvious that people who worked well, and some of them did it themselves. We believe that this problem is related to the lack of information, with one side, and the counteraction to the international one, as well as to the liberal values and constitutional principles of state welfare, with another. To understand this issue, it is necessary to consider the connection between the main and main principles, such as liberalism and the main principles of the socializing state. It is clear that the principle of liberalism assumes diversity. In our practice, we should, say, see that this idea rises to Christianity and anti-philosophy, and its value is a product, say, Western culture and does not have geographical value. That means now. In addition, the disclosure of their thoughts is an answer to the issues of the established Reserve on a higher foreign, say, historical background. The second factor, which should be ignored, is various framed practices, illusions and fantasies, which are present in all spiritual classes with a strong public consciousness, such as the famous, liberal Catechism of the name better, more socialist catechism. Keywords: Social state, Constitution, welfare of the population, civil society, Macroeconomics, citizens ’ rights, democracy, social norms, social protection.